Melatonin Augments the Expression of Core Transcription Factors in Aged and Alzheimer’s Patient Skin Fibroblasts - Shukla, Mayuri; Duangrat, Raphiporn; Nopparat, Chutikorn; Sotthibundhu, Areechun; Govitrapong, Piyarat (Biology (Basel, Switzerland), 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder. Altered neurogenesis and the appearance of AD pathological hallmarks are fundamental to this disease. SRY-Box transcription factor 2 (Sox2), octamer-binding transcription factor 4 (Oct4), and Nanog are a set of core transcription factors that play a very decisive role in the preservation of pluripotency and the self-renewal capacity of embryonic and adult stem cells. These factors are critically involved in AD pathogenesis, senescence, and aging. Skin fibroblasts are emblematic of cellular damage in patients. We, therefore, in the present study, analyzed the basal expression of these factors in young, aged, and AD fibroblasts. AD fibroblasts displayed an altered expression of these factors, differing from aged and young fibroblasts. Since melatonin is well acknowledged for its anti-aging, anti-senescence and anti-AD therapeutic benefits, we further investigated the effects of melatonin treatment on the expression of these factors in fibroblasts, along with precise validation of the observed data in human neuroblastoma SH-SY5Y cells. Our findings reveal that melatonin administration augmented the expression levels of Sox2, Oct4, and Nanog significantly in both cells. Altogether, our study presents the neuroprotective potential and efficacy of melatonin, which might have significant therapeutic benefits for aging and AD patients.